A Coupled Discrete-Finite Element Method for Shear Strength Analysis of Geogrid-Reinforced Railway Ballast. (31st December 2021) - Ji, Danyang; Ma, Zheng; Zhou, Junjie; Li, Yajun; Shao, Shuai
Abstract : This paper presents a coupled discrete-finite element method for the investigation of shear strength of geogrid-reinforced ballast by direct shear tests and pull-out tests. The discrete element method (DEM) and finite element method (FEM) are employed to simulate ballast and geogrid, respectively. Irregularly shaped ballast particles are modeled with clumps, and the nonlinear contact force model is used to calculate contact force between particles. Continuum geogrid is modeled by a two-node beam element with six degrees of freedom. A contact algorithm based on the static equilibrium is proposed at the geogrid-ballast contact surface. The simulation results indicate that shear strengths increase with the installation of geogrid. Moreover, ballast particle displacements and nominal volumetric strains are analyzed to provide a microscopic view on the mechanism of the reinforcement effect of geogrid.